Tațwĩr Ikhtibār Mahārah Al-Istimā‘ Bi Istikhdāmi Tațbĩq Kahoot - Syihabuddin, M.; Abidin, Zainul; Khafifah, Siti (STIQ Amuntai, 2025)
Listening skills play a crucial role in Arabic language acquisition. However, evaluating these skills remains a challenge due to the limited availability of structured and interactive assessment tools. Traditional assessments often lack engagement and fail to accurately measure students’ listening comprehension. This study employs a research and development (R&D) approach using the 4D model, consisting of define, design, develop, and disseminate phases. The objective is to develop and validate a digital listening skills test using the Kahoot application. Data were collected through observation, interviews, and tests involving 20 female students at MA NIPI RAKHA Amuntai. The test was developed with 15 multiple-choice and true-or-false questions and was validated by three experts specializing in Arabic language teaching and educational assessment. The results indicate that the test achieved a high level of validity, with an overall expert rating of 4.65 on a five-point Likert scale, confirming its effectiveness as an evaluation tool. This study contributes to the development of digital assessment tools for Arabic listening skills by validating Kahoot as an interactive and structured evaluation method. Future research should explore its application in broader educational contexts and different proficiency levels, ensuring that such tools enhance the effectiveness of listening assessment in Arabic language education.